Synthesis and release behavior of layered double hydroxides–carbamazepine composites - Peralta, Maria Florencia (2021)
Carbamazepine (CBZ) was incorporated into layered double hydroxides (LDH) to be used as a controlled drug system in solid tumors. CBZ has a formal charge of zero, so its incorporation in the anionic clay implies a challenge. Aiming to overcome this problem, CBZ was loaded into LDH with sodium cholate (SC), a surfactant with negative charge and, for comparison, without SC by the reconstruction method. Surprisingly, it was found that both resultant nanocomposites had similar CBZ encapsulation efficiency, around 75%, and the LDH-CBZ system without SC showed a better performance in relation to the release kinetics of CBZ in simulated body fluid (pH 7.4) and acetate buffer simulating the cellular cytoplasm (pH 4.8) than the system with SC. The CBZ dimensions were measured with Chem3D and, according to the basal spacing obtained from X-ray patterns, it can be arranged in the LDH-CBZ system as a monolayer with the long axis parallel to the LDH layers. Fourier transform infrared spectroscopy and solid state NMR measurements confirmed the presence of the drug, and thermogravimetric analyses showed an enhanced thermal stability for CBZ. These results have interesting implications since they increase the spectrum of LDH application as a controlled drug system to a large number of nonionic drugs, without the addition of other components.